Influence of irrigation with oxygen plasma treated metal contaminated water on plant growth - Sayma Khanom; Nobuya Hayashi (Scientific Reports)
Abstract This study aimed to evaluate the effects of plasma treated metal contaminated water, used for irrigation, on plant growth. Zinc (Zn) is a commonly used metal that can enter the environment through industrial processes. It may be released as particles into the atmosphere or discharged as wastewater into waterways or the ground. Exposure to large amounts of zinc, even for a short duration, can seriously impact human health. In this experiment, three different DBD (dielectric barrier discharge) O2 plasma treated zinc contaminated water and a control (tap water) were used, with Arabidopsis thaliana as the model plant. The treatments were: (i) Control, (ii) Zn water, (iii) Zn + O3(30 min), and (iv) Zn + O3(60 min). Arabidopsis plant exhibited maximum growth in the Zn + O3(30 min) treatment. All growth parameters, except leaf area, followed this trend: Zn + O3(30 min) > Control > Zn water > Zn + O3(60 min). Gene expression analysis revealed that reduced metal ion stress and controlled oxidation due to active oxygen species contributed to favorable/improved growth of Arabidopsis in the Zn + O3(30 min) treatment. Therefore, 30 min of DBD O2 plasma treated zinc contaminated water [Zn + O3(30 min)] can mitigate the adverse effects of excess zinc ions and promote the growth of Arabidopsis plants.